Determinants affecting personal financial management behaviors among generation Y: a case study in Wilayah Persekutuan Kuala Lumpur / Khairul Anwar Mohd Azmi - Mohd Azmi, Khairul Anwar (2017)
They have the world at their fingertips which is referred to Generation Y. They are outfitted with noteworthy paper, capabilities and furnished with an aggressive edge, Generation Y 's has a simple and quick access to all the modern technologies that they can without much of a stretch have the way of life they had always wanted. This study aim to investigate the Determinants Affecting Personal Financial Management Behaviour among Gen Y in Kuala Lumpur. The independent variables used to determine the relationships are Financial Attitude, Financial Knowledge, and External Locus of Control. This research was carried out in Kuala Lumpur where 100 respondents were used as sample of the study to answer the questionnaire. Multiple Linear Regression was used for measuring the relationship and to test whether the model is accepted or not. From the findings, all the independents variable are significantly positive related and showed direct effect towards financial management behaviour. However it only explained 32% of the variance in the dependant variable. These findings could be useful for individual's references and for future researcher but further studies need to be conducted to provide better clarification about this study.